Pengembangan Alat Evaluasi Berbantuan Aplikasi Gimkit pada Materi Teks Laporan Hasil Observasi pada Siswa Kelas X Sekolah Menengah Atas Negeri 1 Raya Kahean - Ayu Lela Sari; Rika Kartika; Ratna Soraya (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study addresses the limited use of interactive digital evaluation tools in assessing students’ mastery of observation report texts by developing a Gimkit-assisted learning evaluation tool for tenth-grade students at State Senior High School One Raya Kahean, Simalungun Regency. The study seeks to determine the feasibility and effectiveness of the developed tool in supporting Indonesian language learning assessment. Employing a Research and Development approach, the study adopted the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The research involved a population of 124 students, with a sample of 30 students, and included validation by a material expert, a design expert, an Indonesian language teacher, and student users. The findings demonstrate that the evaluation tool achieved a high level of feasibility, with material expert validation reaching 88.33 percent and design expert validation reaching 89.66 percent. In addition, the effectiveness assessment conducted by the Indonesian language teacher yielded a score of 92 percent, indicating a highly effective category. The study argues that integrating gamified digital applications such as Gimkit into evaluation practices enhances assessment quality, student engagement, and instructional relevance, making the tool a viable and effective alternative for school-based learning evaluation.